Dilemma of Conservation and Exploitation: The Threat of Ecosystem Damage on Nusa Kambangan Island as the Lungs of Java - Zhalfa Salsabila Rudianto Putri; Kirana Nabila Putri Agrivani; Nuur Muchlis Tsalaatsa; Dyah Astriani; Fikky Dian Roqobih (Fakultas Kehutanan, Universitas Hasanuddin, 2026)
This article examines the dilemma between conservation and exploitation on Nusa Kambangan Island, a protected nature reserve in Java. A systematic literature review (SLR) was conducted by searching nationally accredited Indonesian journals using keywords such as “Nusa Kambangan,” “conservation,”, “karst ecosystem,” and “mangrove.” A preliminary 34 publications were screened based on relevance, year (2016–2025), language, and source credibility, resulting in seven selected articles that met the inclusion criteria. The findings indicate that Nusa Kambangan harbors critical ecosystems including lowland tropical forests, karst cave systems, and the Segara Anakan mangroves, which collectively support biodiversity and ecological balance. Pressures from deforestation, limestone mining, prison operations, and water pollution have led to ecosystem degradation. Conservation efforts through government regulations, ecosystem rehabilitation, and local wisdom-based management have been implemented but face challenges. An integrated governance-based management strategy is recommended to align conservation and development interests.